Quality Control Analysis, Standardization And Stability Studies Of Eurycoma Longifolia And Effect Of Its Saponin Content On Solubility And Toxicity Of Eurycomanone - Khari, Nursyazura (2014)
Quality control test was done on E. longifolia root, stem and leaf from five different localities in order to determine the range of quality control values. Moisture, ash and acid insoluble ash content of all the root raw material were found to be within acceptable limit set by Standard of Asean Herbal Medicine and Malaysian Herbal Monograph Volume 1. Ujian kawalan kualiti dilakukan pada bahan mentah akar, batang dan daun E. longifolia daripada lima lokasi yang berbeza untuk menentukan julat nilai kawalan kualiti. Kandungan kelembapan, abu dan abu tidak larut asid bagi akar berada di dalam julat yang ditetapkan oleh Standard Perubatan Herba Asean dan Monograf Herba Malaysia Jilid 1.